2019
DOI: 10.2106/jbjs.rvw.18.00198
|View full text |Cite
|
Sign up to set email alerts
|

The Menstrual Cycle May Affect Anterior Knee Laxity and the Rate of Anterior Cruciate Ligament Rupture

Abstract: Background: Women have a higher risk of anterior cruciate ligament (ACL) tears than men, the causes of which are multifactorial. The menstrual cycle and its hormonal effect on the knee may contribute to knee laxity and ACL injury. This work reviewed published studies examining the effects of the phases of the menstrual cycle on anterior knee laxity and the rate of ACL tears.Methods: A systematic review with meta-analysis and meta-regression was performed. Studies with data comparing the menstrual cycle phase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 56 publications
0
38
1
1
Order By: Relevance
“…The presence of sex hormones or relaxing receptors in ACL might explain their effect on this structure, but other extrinsic or intrinsic factors may contribute to this process [ 79 , 80 ]. Recent reviews [ 81 , 82 ] seem to show a decreased risk of ACL injury during L vs. F and PeO, with increased ACL laxity in PeO at high E2 levels vs. other MC phases. However, no association was found between increased risks of ACL tears and increased laxity [ 82 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of sex hormones or relaxing receptors in ACL might explain their effect on this structure, but other extrinsic or intrinsic factors may contribute to this process [ 79 , 80 ]. Recent reviews [ 81 , 82 ] seem to show a decreased risk of ACL injury during L vs. F and PeO, with increased ACL laxity in PeO at high E2 levels vs. other MC phases. However, no association was found between increased risks of ACL tears and increased laxity [ 82 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…Recent reviews [ 81 , 82 ] seem to show a decreased risk of ACL injury during L vs. F and PeO, with increased ACL laxity in PeO at high E2 levels vs. other MC phases. However, no association was found between increased risks of ACL tears and increased laxity [ 82 ]. Moreover, other authors have reported no significantly different ACL laxity in high-level female athletes in F, PeO, and L, at rest or during exercise [ 83 , 84 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…A recent systematic review with meta-analysis concluded an increased risk of ACL tear does not appear to be associated with periods of increased laxity. The results showed anterior knee translation was the lowest during the follicular phase (days 1-9) compared to the ovulatory phase (days [10][11][12][13][14] or the luteal phase (days 15-28) [20]. During the ovulatory phase, the surge in estradiol has been shown to decrease fibroblast proliferation and collagen synthesis, thus increasing knee laxity.…”
Section: Discussionmentioning
confidence: 98%
“…There is also evidence that the menstrual cycle may affect anterior knee laxity and the risk of ACL rupture. It is estimated that women have a two to four-fold increased risk of ACL tear compared to men; however, how much of this risk is related to hormonal fluctuations remains unclear [20]. The direct associations between the menstrual cycle and ACL injury remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has been postulated that the increased ligamentous laxity seen during the ovulatory phase of the menstrual cycle may be part of the reason why there are gender-specific differences seen in the prevalence of tendon injury and joint disease. [12][13][14] In particular, anterior cruciate ligament laxity has been shown to be significantly increased with peak levels of estrogen and progesterone during the menstrual cycle. 12 Relaxin is a hormone that circulates at low concentrations in the nonpregnant state, but during pregnancy, relaxin is secreted by the corpus luteum and from the placenta.…”
Section: Discussionmentioning
confidence: 99%